Direct ink write multi-material printing of PDMS-BTO composites with MWCNT electrodes for flexible force sensors. (11th January 2022) - Renteria, Anabel; Balcorta, Victor H; Marquez, Cory; Rodriguez, Aaron A; Renteria-Marquez, Ivan; Regis, Jaime; Wilburn, Bethany; Patterson, Steven; Espalin, David; Tseng, Tzu-Liang (Bill); Lin, Yirong
Abstract: With recent advances of additive manufacturing technology, direct ink write (DIW) printing has allowed to incorporate multi-material printing of various materials with freedom of design and complex geometric shapes to complete functional sensors in a one-step fabrication. This paper introduces the use of DIW 3D printing of polydimethylsiloxane (PDMS) with barium titanate (BTO) filler as stretchable composites with tunable piezoelectric properties that can be used for force sensors applications. To improve the bonding between stretchable piezoelectric composites and electrodes, multi-walled carbon nanotubes was included in the fabrication of electrodes at a fixed ratio of 11 wt. %. The alignment of the BTO dipoles was achieved through corona poling method, which applies an electric charge on the surface layer of the functional material, aligning the dipoles in the desired direction and thus gaining the piezoelectricity. Different BTO mixing ratios (10–50 wt. %) were evaluated in order to obtain tunable piezoelectric properties and compare the sensitivity with respect their elastic properties. Tensile testing and piezoelectric testing were carried out to characterize mechanical and piezoelectric properties. Results showed that fabricated PDMS with 50 wt. % BTO gave the highest piezoelectric coefficient ( d 33 ) of 11.5 pC N −1 and with an output voltage of 385 mV under compression loading of >200 lbF. This demonstrates feasibility of using multi-material DIW printing to fabricate piezoelectric force sensors with integrated electrodes in one-step without compromising the flexibility of the material.